Virus, a whole case, but not lost - Mata Villalpando-Becerra, Isaac (Universidad Autónoma de Tamaulipas, 2010)
Malware Malicious software includes viruses, worms and Trojans. Its severity ranges from jokes to be attacks that cause loss of data, equipment damage, denial of services and economic losses. It originated in the beginning of computing to mid-twentieth sophistication, and affecting the Internet, to all platforms and all operating systems, mainly to Microsoft Windows because of its great popularity and commercial. To expand, the malware used primarily social engineering (practice of obtaining confidential information through the manipulation of people), instant messaging and social networks. Putting into practice methods and response prevention tips can successfully mitigate the risks.